Attenuation of Renal Functional Decline Following Angioplasty and Stenting in Atherosclerotic Renovascular Disease - Hagemann, Rodrigo [UNESP]; Dos Santos Silva, Vanessa [UNESP]; Cardoso Carvalho, Fábio [UNESP]; Barretti, Pasqual [UNESP]; Martin, Luis Cuadrado [UNESP]; Vassallo, Diana [UNESP]; Kalra, Philip A. [UNESP]; Da Silva Franco, Roberto Jorge [UNESP] (Karger Publishers, 2017)
Background: To date, renal revascularization has not been shown to be advantageous when compared to optimized medical treatment in patients with atheromatous renovascular disease (ARVD). This study aims to investigate the effect of revascularization in patients with pre-intervention worsening renal function and in those with stable renal function. Patients and Methods: In this single-centre observational study, patients who were diagnosed with at least 60% angiographic stenosis unilaterally or bilaterally between January 1996 and October 2008 and who were followed-up until February 2011 were retrospectively analysed. Evolution of renal function was determined from the slope of reciprocal of serum creatinine (RCr-slope) before and after diagnostic angiography or revascularization; this required 5 or more creatinine measurements before and at least another 5 measurements post-procedure. Patients were divided into 2 groups: one comprising patients with negative RCr-slope before the procedure and a second group of patients with prior positive RCr-slope. A stepwise, adjusted logistic regression was used to determine the OR of revascularization on attenuation of RCr-slope. Results: Data for 52 patients were analysed. Median age was 64 (58-72) and median follow-up was 15 (8-34) months. Only patients with a negative RCr-slope (-0.0078 (95% CI -0.0174, -0.0033) dl/mg/month) who underwent revascularization manifested an improved RCr-slope during follow-up (+0.0013 (95% CI -0.0002, 0.0039) dl/mg/month, p < 0.001). This finding remained statistically significant even after the adjustment for proteinuria and bilateral arterial disease. Conclusion: Revascularization may be indicated for patients with ARVD and progressively worsening renal function. This patient subgroup should ideally be evaluated in future randomized controlled trials.
Keywords: Atherosclerotic renovascular disease; Chronic kidney disease progression; End-stage kidney disease; Revascularization